PSYCHOLOGICAL ASSISTANCE IN CRISIS AND MILITARY CHALLENGES: PROBLEMS OF TRAINING SPECIALISTS - Spivak, Yaroslav; Spivak , Liudmyla; Omelchenko, Svitlana (The Modern Higher Education Review, 2025)
The article examines both the theoretical and practical aspects of providing psychological support during crises and military conflicts, highlighting the emerging demands for the professional training of psychology specialists. It stresses that the ongoing socio-military climate in Ukraine has created a pressing need for psychologists capable of functioning effectively amid heightened stress, uncertainty, and widespread trauma experienced by the population. The study aims to provide a theoretical foundation for the organizational and pedagogical conditions essential for preparing future psychologists for crisis intervention. A review of international and domestic methodologies related to training specialists in crisis psychology is conducted, particularly focusing on contexts involving combat situations, forced migrations, losses, and post-traumatic effects. The article outlines the key structural components that constitute a future psychologist’s professional readiness: cognitive (understanding crisis dynamics and trauma), operational-behavioural (skills in delivering first aid and counselling under extreme conditions), emotional-volitional (stress management, empathy, self-regulation), and ethical (respect for clients, confidentiality, accountability). The empirical section presents findings from the execution of a practice-oriented training model, which features simulation exercises such as "Crisis Scene," "Breathing Under Pressure," and "Ethical Dilemma." These exercises are designed to enhance stress resilience, uphold professional ethics, and foster quick decision-making abilities in crisis scenarios. Results indicate a notable increase in students’ confidence regarding their professional capabilities, along with improvements in self-regulation skills and heightened ethical awareness. The necessity for reforming the psychologist training system within higher education institutions is supported through an interdisciplinary approach that incorporates modern educational technologies – such as online courses, simulation labs, and supervision – and establishes a support framework for emerging professionals. The conclusion drawn is that cultivating the professional readiness of future psychologists to operate effectively during crises and warfare represents not only an educational imperative but also a societal necessity that impacts the overall psychological security of the community.